2018
DOI: 10.2174/1874091x01812010046
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Restorative Effects of Nutrients and Phytochemicals

Abstract: Intoroduction:Dietary intake fundamentally provides reintegration of energy and essential nutrients to human organisms. However, its qualitative and quantitative composition strongly affects individual’s health, possibly being either a preventive or a risk factor. It was shown that nutritional status resulting from long-term exposition to specific diet formulations can outstandingly reduce incidences of most common and most important diseases of the developed world, such as cardiovascular and neoplastic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 168 publications
0
11
0
1
Order By: Relevance
“…Among them, to date, the following pathways have been identified: the inhibition of the DNA binding of carcinogens, the stimulation of detoxification of potentially damaging compounds, DNA repair, the repression of cell proliferation and angiogenesis (directly related to tumor growth and metastasis), the induction of apoptosis of malignant cells [ 37 , 38 ], and the ability to enhance the antioxidant tools of cells and promote free radical scavenging [ 39 , 40 ]. Regarding this biological activity, the modulation of the inflammatory cascade, and more specifically, the transcription factor NF-κB by GLSs, ITCs, and (poly)phenols, are also involved in the anticancer activity [ 41 ]. Hence, hereafter, the evidence on the value of incorporating cruciferous sprouts to regular diets to prevent a number of clinical situations is reviewed ( Table 3 ), and the molecular mechanisms involved are also discussed.…”
Section: The Challenges Of Including Cruciferous Sprouts In Balancmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, to date, the following pathways have been identified: the inhibition of the DNA binding of carcinogens, the stimulation of detoxification of potentially damaging compounds, DNA repair, the repression of cell proliferation and angiogenesis (directly related to tumor growth and metastasis), the induction of apoptosis of malignant cells [ 37 , 38 ], and the ability to enhance the antioxidant tools of cells and promote free radical scavenging [ 39 , 40 ]. Regarding this biological activity, the modulation of the inflammatory cascade, and more specifically, the transcription factor NF-κB by GLSs, ITCs, and (poly)phenols, are also involved in the anticancer activity [ 41 ]. Hence, hereafter, the evidence on the value of incorporating cruciferous sprouts to regular diets to prevent a number of clinical situations is reviewed ( Table 3 ), and the molecular mechanisms involved are also discussed.…”
Section: The Challenges Of Including Cruciferous Sprouts In Balancmentioning
confidence: 99%
“…The ITCs phenethyl isothiocyanate (PEITC), benzyl isothiocyanate (BITC), and SFN, have been demonstrated to have chemo-preventive activity in diverse in vitro models, exhibiting multi-target activities in cells and tissues [ 41 ]. Early works of Fahey et al (1997) demonstrated the capacity of broccoli sprouts to reduce the incidence of breast cancer in vivo due to the presence of ITCs acting as inducers of enzymes that protect against carcinogens.…”
Section: The Challenges Of Including Cruciferous Sprouts In Balancmentioning
confidence: 99%
“…The first questionnaire collected data on demographic characteristics, physical activity (engagement in any type of exercise for at least 30 min), diagnosis of depression (patients previously diagnosed by a psychiatrist according to the DSM-IV), and antidepressant medication use. The second questionnaire evaluated the intensity of depression symptoms, measured using the Beck Depression Inventory (BDI), classified as: normal (0-9), mild (10)(11)(12)(13)(14)(15), mild to moderate (16)(17)(18)(19), moderate to severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), or severe (30-63). 23 Information about the diet of the volunteers was obtained using a 24-hour dietary recall.…”
Section: Methodsmentioning
confidence: 99%
“…19,20 Previous evidence shows that antioxidants present in foods from natural sources can influence brain dynamics and functioning through a preventive and/or therapeutic effect elicited by these compounds. 10,13,21,22 While dietary phytochemicals promote an important either preventive or restorative effect in several chronic diseases, their role in depression needs further investigation. Furthermore, information about the intake of antioxidants by women is scarce.…”
mentioning
confidence: 99%
“…It is important to take food 3-4 hours before the competition, to prevent and monitor dehydration by ingesting, 30-40 minutes before the competition, a supplement in the form of a drink and, in the post-race phase, is necessary to reintegrate the water reserves, assuming a quantity of liquids equal to the kg lost plus another 50%, as well as glycogen, taking 1gr of glucose per body weight, accumulated in pre-race (Galanti, Stefani, Scacciati et al, 2015;Altavilla et al, 2018). The reintegration of energy and water reserves must be controlled in order to avoid the absorption of high doses of supplements, or associations of supplements or a consumption of them for a long period, which can cause damage to the liver, kidney and heart (Rescigno et al, 2018). These conditions together with an imbalance between training and recovery loads cause a dysfunction of the neuroendocrine system at the hypothalamic level determining the overtraining conditions.…”
Section: Introductionmentioning
confidence: 99%